2005
DOI: 10.1128/aem.71.9.5192-5196.2005
|View full text |Cite
|
Sign up to set email alerts
|

13 C-Carrier DNA Shortens the Incubation Time Needed To Detect Benzoate-Utilizing Denitrifying Bacteria by Stable-Isotope Probing

Abstract: The active bacterial community able to utilize benzoate under denitrifying conditions was elucidated in two coastal sediments using stable-isotope probing (SIP) and nosZ gene amplification. The SIP method employed samples from Norfolk Harbor, Virginia, and a Long-Term Ecosystem Observatory (no. 15) off the coast of Tuckerton, New Jersey. The SIP method was modified by use of archaeal carrier DNA in the density gradient separation. The carrier DNA significantly reduced the incubation time necessary to detect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 30 publications
2
76
2
Order By: Relevance
“…In 83% of the microcosms, bacterial 13 C-DNA synthesis was observed, except for the low concentrations of urea and ISOGRO (Table 2). The relatively long SIP incubation time (5 days) most likely allowed for extensive crossfeeding between the bacteria (Gallagher et al, 2005) and the generation of 13 C-CO 2 (data not shown). To test whether the crenarchaea were actually taking up 13 CO 2 rather than the 13 C-labeled substrates during our SIP experiment, a 13 C-bicarbonate incubation was also conducted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 83% of the microcosms, bacterial 13 C-DNA synthesis was observed, except for the low concentrations of urea and ISOGRO (Table 2). The relatively long SIP incubation time (5 days) most likely allowed for extensive crossfeeding between the bacteria (Gallagher et al, 2005) and the generation of 13 C-CO 2 (data not shown). To test whether the crenarchaea were actually taking up 13 CO 2 rather than the 13 C-labeled substrates during our SIP experiment, a 13 C-bicarbonate incubation was also conducted.…”
Section: Resultsmentioning
confidence: 99%
“…DNA was extracted by phenolchloroform methods and fractionated by isopycnic cesium chloride gradient ultracentrifugation at 200 000 g for 36 h, with 13 C-labeled Halobacterium salinarum as a carrier when detecting bacterial DNA or 13 C-Escherichia coli DNA when targeting archaeal DNA (Gallagher et al, 2005). After ultracentrifugation, the 12 C-and 13 C-bands were collected by pipette and amplified by PCR using 5 0 -fluorescently labeled, archaea-specific (21F, 5 0 -TTCCGGTTGATCC YGCCGGA-3 0 /958R, 5 0 -YCCGGCGTTGAMTCCAAT T-3 0 ) and crenarchaeota-specific (7F, 5 0 -TTCCGGTT GATCCYGCCGGACC-3 0 /518R, 5 0 -GCTGGTWTTACC GCGGCGGCTGA-3 0 ) or bacteria-specific forward/ reverse primers (27F, 5 0 -AGAGTTTGATCCTGGCT CAG-3 0 /1100R, 5 0 -AGGGTTGCGCTCGTTG-3 0 ) targeting the 16S rRNA gene.…”
Section: Methodsmentioning
confidence: 99%
“…This was immediately followed by a 2 Â phenol/ chloroform extraction. Purified DNA (200-300 ng) was then subjected to cesium chloride (CsCl) isopycnal centrifugation (225 000 g for 48 h) with 100 ng of archaeal (Halobacterium salinarum) 13 C-carrier DNA, which has been shown to reduce the amount of 13 C-incorporation necessary for signal detection in an SIP experiment (Gallagher et al, 2005). This carrier/SIP approach yields a 12 C (top) band and a 13 C (bottom) band for all microcosm incubations, representing the resident ( 12 C) and the active ( 13 C) bacterial community, respectively (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, especially the use of stable isotopes in combination with molecular tools has enabled researchers to identify such key anaerobic contaminant degraders, not only in enrichments stemming from aquifers (Kasai et al, 2006;Kunapuli et al, 2007;Bombach et al, 2010;Herrmann et al, 2010), but also from a wide variety of other sediments and soils (Gallagher et al, 2005;Kittelmann and Friedrich, 2008;Liou et al, 2008;Oka et al, 2008). Stable isotope probing (SIP) of nucleic acids allows for the specific identification of microorganisms catabolizing and assimilating carbon from a particular 13 C-labeled substrate, and if performed for DNA, also to identify and affiliate involved catabolic genes on labeled genomes (Jeon et al, 2003;Leigh et al, 2007).…”
Section: Introductionmentioning
confidence: 99%